Effects of polysaccharide charge pattern on the microstructures of β-lactoglobulin-pectin complex coacervates, studied by SAXS and SANS. (April 2018) - Xu, Amy Y.; Melton, Laurence D.; Ryan, Timothy M.; Mata, Jitendra P.; Rekas, Agata; Williams, Martin A.K.; McGillivray, Duncan J.
Abstract: Protein and polysaccharide complex coacervates have been widely used in developing complex food products, the function as well as the physicochemical properties of these food materials are closely related to the microstructure of the coacervates. To this end, the effects of the total amount and distribution of charges carried by pectic polysaccharides on the microstructure of complex coacervates formed through interactions with the protein, bovine β-lactoglobulin variant A (βLgA) were investigated. Small angle X-ray and neutron scattering reveal the major building blocks of complex coacervates are compact primary particles. These primary particles are composed of overlapping protein-binding pectin chains, bridged by βLgA-rich clusters. The overall and local charge densities of pectin influence the size and distribution of βLgA-rich clusters within the primary particles. Moreover, depending on the spatial arrangements of the primary particles, the resulting structure could be either a complex coacervate or a precipitate. Results represented in this study imply the possibility of controlling the microstructure of protein-polysaccharide complex coacervates using polysaccharides with various charge patterns. Graphical abstract: Image 1 Highlights: Scattering results reveal the presence of multi-length structural elements that together constitute complex coacervates. Primary particles consisting overlapped pectin chains and βLgA-rich clusters are the major building blocks for coacervates. Overall and local charge densities of pectin affect the size and distribution of βLgA-rich clusters respectively.